Role of Standardized Patients in Medical Education - Khanam, Nurun Nahar (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
The objective of this study is to aware medical faculties about the advantages of use of Standardized patients in medical education. It is a review paper, written after reviewing the articles on “Standardized Patients in medical education” Standardized Patients (SPs) are healthy individuals who are trained to simulate real patients in a realistic and reliable manner. SPs perform several roles in medical education like, they help medical learners to learn and be evaluated all domains of clinical medical competence effectively without debilitating the real patients, they can be sent unannounced in physician practices to evaluate standards of care, they can also use in health informatics research, etc. Use of SPs are advantageous over real patients in terms of convenience, standardization, compression/expansion of time, safety, feasibility, efficiency, skill transfer, feedback, tolerance, critical care or team training, integrated procedural performance instrument (IPPI), and evaluation of rare diseases. There are some inconveniencies as well, for example, recruiting and giving high-quality training is time consuming and costly, SPs can never replace the rich encounter with an actual patient, simulation of all physical signs is not possible, and above all some examiners may not like SPs in the examination. Considering all the facts it can be concluded that standardized patients are unquestionably valuable implements in medical education both for teaching and assessment. It is not to replace the real patients from the medical education but to produce a safe bridge between medical students and novice doctors with real patients. Bangladesh J Obstet Gynaecol, 2021; Vol. 36(2): 126-131